Life‐Years & Rationing in the Covid‐19 Pandemic: A Critical Analysis. Issue 5 (16th September 2021) - Gaurke, MaryKatherine; Prusak, Bernard; Jeong, Kyeong Yun; Scire, Emily; Sulmasy, Daniel P.
Abstract: Prominent bioethicists have promoted the preservation of life‐years as a rationing strategy in response to the Covid‐19 pandemic. Yet the philosophical justification for maximizing life‐years is underdeveloped and has a complex history that is not reflected in recent literature. In this article, we offer a critical investigation of the use of life‐years, arguing that evidence of public support for the life‐years approach is thin and that organ transplantation protocols (heavily cited in pandemic‐response protocols) do not provide a precedent for seeking to save the most life‐years. We point out that many state emergency‐response plans ultimately rejected or severely attenuated the meaning of saving the most life‐years, and we argue that philosophical arguments in support of rationing by life‐years are remarkably wanting. We conclude by offering a fair alternative that adheres to the standard duties of beneficence, respect for persons, and justice .